KAJIAN TANGGUNGJAWAB HUKUM DEVELOPER AKIBAT TIDAK DIBANGUNNYA KONDOTEL SESUAI PERJANJIAN - Suwardi (Faculty of Law, University of Dr. Soetomo, 2022)
As developers occupancy kondotel providers have responsibility law null pre transactions .So law developers responsibility to consumer on pre the transaction will give rise to rights prospective buyers and delivery also obligation and responsibilities entrepreneurs to meet hak-hak consumers. Article 129 (a) the act act number 1 year 2011 residential about housing and stated that in the housing and residential compound, everyone has the right to, enjoy, and / or having / have. How to four responsibility according to the agreement made ? Methods used is normative, which refers and set out in article of the year - 129 no.1 2011. Dwelling kondotel responsibility of the developer to consumers from agreement on the transaction condotel are carried between developer with consumers Keyword : Developers not responsibility according to the agreement